Experimental investigation of erosion caused by gas-borne ash particles - Shandu, Richard Dumisani (My University, 2008)
A test facility was constructed to conduct experimental investigation of erosion caused by gas-borne ash particles. The test facility was used to carry out the main objective of the study which was the determination of the critical angle of attack that gives maximum erosion on the target material, mild steel, and the effect of particle velocity and concentration on the erosion of the target material. The tests were carried out using ash samples from three different Eskom fossil-fuelled power stations, namely Matimba Power Station, Matla Power Station and Lethabo Power Station. The selection of the ash samples was based on the ash chemical composition that has the highest content of the chemical elements that have a significant influence in the material erosion of the target material. These chemical elements are quartz and other abrasive materials. These ash samples had a high content of these erosive materials. The first test that was carried out in this study was the determination of the critical angle of attack that gives maximum erosion on the target material. It was decided to start by doing this test because the velocity and concentration tests needed a predefined critical angle of attack that gives maximum erosion on the target material. During the velocity and concentration tests the angle of attack was kept at the predefined critical angle of attack. The results in this study indicate that the critical angle of attack that gives maximum erosion on the target material is at 27º ± 3º orientation of the target surface. The velocity test results indicate that the material erosion rate increases with increasing velocity. The results produced a power relationship between erosion rate and velocity. In this power relationship the velocity exponent for the three ash samples was found to be in the range between 2.42 and 3.64. The concentration test results also indicate that the material erosion rate increases with increasing particle concentration. These results produced a linear relationship between erosion rate and particle concentration.
Keywords: gas-borne ash particles; erosion